Adhesive-free fiberboard and preparation method thereof

Through the combination of oxidation treatment and metal ion feeding combined with polyphenol, it is prepared to prepare a glue -free fiber board, solving the problems of complex preparation processes in the existing technology, and achieved efficient, environmentally friendly, and low -cost glue -free fiber board preparation.

CN119347911APending Publication Date: 2025-01-24泰州大自然家居有限公司

Patent Information

Application Number
CN202411571885.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing preparation methods of rubber-free fiberboard have problems such as complex production processes, high energy consumption, difficult chemical recycling, and large environmental load, resulting in high production costs.

Method used

By oxidizing the wood fiber, placed in a metal ion solution for non -co -price keys to treat, and chelated with polyphenols to form self -adhesive chelated fibers. Essence

Benefits of technology

The simple and easy preparation of glue -free fiber plates is achieved, reducing energy consumption and chemical use, improving the density and stability of the materials, excellent mechanical properties, and zero formaldehyde release, more environmentally friendly and low cost.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention is suitable for the technical field of materials, and provides a binderless fiberboard and a preparation method thereof.The preparation method comprises the steps that wood fibers are subjected to oxidation treatment, and an intermediate is obtained; placing the intermediate in a metal ion solution for non-covalent bond coordination treatment, extruding the solution, and adding polyphenol into the fiber for chelation to obtain a chelated fiber; and assembling the chelate fibers into a plate blank, and carrying out hot pressing treatment to obtain the product. Metal ions and lignin hydroxyl are bonded and coordinated through an activation method, then the metal ions and polyphenol are chelated to form self-adhesion, meanwhile, the non-adhesive fiberboard formed by tightly interweaving and stacking the fibers can reach the national standard in mechanical strength and water absorption expansion rate, the preparation method is simple and easy to implement, raw materials are easy to obtain, and the production cost is low. The method is suitable for mass production; by means of the formed double-network structure, the binderless fiberboard is more compact, higher in stability and excellent in internal bonding strength, bending strength and other mechanical properties. Zero formaldehyde release of the fiberboard is achieved, and the cost is lower.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of material technology, and in particular relates to a glue-free fiberboard and a preparation method thereof. Background Art

[0002] Traditional fiberboard is a board made by mixing wood fiber and other fiber materials with adhesives and pressing them under high temperature and pressure. It contains adhesives, and most of the adhesives are made of synthetic resins, such as phenolic resins and urea-formaldehyde resins. Traditional synthetic resin adhesives contain a large amount of free formaldehyde, which not only causes air pollution, but also has great harm to people's health. Glue-free plywood uses composite additives to replace traditional chemical products such as synthetic resin adhesives. During the hot pressing process, the cross-linking effect between the components of the composite filler raw materials themselves achieves bonding. It does not contain harmful substances such as formaldehyde and is a green product that does not pollute the environment and the human body.

[0003] Glue-free fiberboard is usually made by pressing wood fibers under high pressure without adding adhesives. This makes glue-free fiberboard more environmentally friendly because it does not release volatile organic compounds (VOCs) that may be brought by adhesives. Therefore, more and more research is devoted to the development of adhesive-free artificial board preparation methods.

[0004] The patent document with publication number CN117464800A discloses a non-glue fiberboard and its preparation method, which belongs to the field of artificial board technology. The invention uses agricultural and forestry waste as raw materials to prepare fibers with a large aspect ratio, separates the components of the straw raw materials through an organic solvent containing a small molecule auxiliary agent, and while separating the components, the small molecule auxiliary agent activates the dissolved lignin and hemicellulose in situ, and the separated and activated mixture is evaporated, concentrated, and dried, and the activation products of lignin and hemicellulose in the organic solvent gradually precipitate on the solid surface of cellulose fibers, reassemble with cellulose solids, and obtain a cellulose fiber solid material self-assembled and coated with the activation product, and the dried solid material is hot-pressed.

[0005] In summary, the existing preparation methods of non-glue fiberboard generally go through a relatively complicated production process. The existing process technology has problems such as high energy consumption, difficulty in recycling chemicals, and high environmental load, which greatly increases the production cost of fiberboard. Therefore, it is urgent to develop a new type of non-glue fiberboard that is green, environmentally friendly, safe, reliable, and has strong mechanical properties that can be prepared by a simple method. Summary of the invention

[0006] The purpose of the embodiments of the present application is to provide a method for preparing a glue-free fiberboard, aiming to solve the problems of the existing method for preparing a glue-free fiberboard, such as complex production process, high energy consumption, difficulty in recycling chemicals, and high environmental load.

[0007] The embodiment of the present application is implemented as follows: a method for preparing a glue-free fiberboard comprises:

[0008] The wood fiber is subjected to oxidation treatment to obtain an intermediate;

[0009] The intermediate is placed in a metal ion solution for non-covalent coordination treatment, the solution is squeezed out, and polyphenol is added to the obtained fiber for chelation to obtain chelated fiber;

[0010] The chelated fibers are assembled into a board blank, and subjected to a heat pressing treatment to obtain a non-glue fiberboard.

[0011] Preferably, the non-covalent coordination treatment time is 6-24 hours.

[0012] Preferably, the mass ratio of the fiber to the polyphenol is 4:1-2:1.

[0013] Another object of an embodiment of the present application is to provide a glue-free fiberboard, wherein the glue-free fiberboard is prepared by the above-mentioned method for preparing the glue-free fiberboard.

[0014] The preparation method of the glue-free fiberboard provided in the embodiment of the present application adopts an activation method to make the metal ions bond and coordinate with the hydroxyl groups of lignin, and then chelate with polyphenols to form self-bonding. At the same time, the fibers are tightly interwoven and stacked to form the glue-free fiberboard, which not only has mechanical strength and water absorption expansion rate that can meet national standards, but also has a simple and easy preparation method, and the raw materials are easy to obtain, which is suitable for mass production; wherein, the formed double network structure makes the glue-free fiberboard denser, more stable, and has excellent mechanical properties such as internal bonding strength and bending strength, and has broad application prospects; in addition, the present application achieves zero formaldehyde release of the fiberboard, and the prepared glue-free fiberboard is more environmentally friendly than commercial fiberboard, is better than most of the reported fiberboards, and has the advantage of low cost. DETAILED DESCRIPTION

[0015] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.

[0016] The present invention provides a method for preparing a non-glue fiberboard, comprising the following steps:

[0017] The wood fiber is subjected to oxidation treatment to obtain an intermediate;

[0018] The intermediate is placed in a metal ion solution for non-covalent coordination treatment, the solution is squeezed out, and polyphenol is added to the obtained fiber for chelation to obtain chelated fiber;

[0019] The chelated fibers are assembled into a board blank, and subjected to a heat pressing treatment to obtain a non-glue fiberboard.

[0020] In the embodiment of the present application, the wood fiber can be any one or more fibers such as poplar, pine, willow, walnut, etc. Although the specific embodiment of the present application only uses poplar, pine, willow fibers (weight 0.30-0.42g / cm 3 ) is taken as an example, but this should not limit the scope of protection of the present application. Those skilled in the art can choose other wood fibers to replace them according to actual conditions.

[0021] In an embodiment of the present application, the step of oxidizing the wood fiber to obtain an intermediate includes: soaking the wood fiber in a chemical solution, heating and oxidizing the solution, and washing the solution to obtain the intermediate.

[0022] The chemical solution used for the oxidation treatment may be phosphate buffered saline (PBS buffer), sodium chlorite (NaClO 2 ), an aqueous solution mixed with 2,2,6,6-tetramethylpiperidinium oxide (TEMPO) and sodium hypochlorite solution (NaClO), preferably, the maximum range of the chemical ratios in 2000mL of water are 10-20g of phosphate buffer, 10-20g of sodium chlorite, 0.14-0.28g of 2,2,6,6-tetramethylpiperidinium oxide, and 2.9-5.8mL of sodium hypochlorite solution.

[0023] Among them, too low oxidation treatment temperature will lead to insufficient reaction activity of the system, but too high temperature will cause decomposition of weak acid and its intermediates. Therefore, the oxidation treatment temperature is preferably 50-90°C, and the oxidation treatment time is 1-24h.

[0024] In the embodiment of the present application, the metal ion solution can be one or more of sodium chloride solution, aluminum chloride hexahydrate solution, and cobalt chloride hexahydrate solution; the salt concentration is preferably 5-10%. The volume mass ratio of the metal ion solution to the fiber is preferably 4-8:100.

[0025] In the examples of the present application, in order to ensure sufficient coordination, the non-covalent coordination treatment time is required to be greater than 6 hours. Taking the metal ion solution as a sodium chloride solution as an example, the non-covalent coordination refers to the coordination of lignin hydroxyl groups with sodium ions, and the treatment time is 6-24 hours.

[0026] In the embodiment of the present application, polyphenols are added to the obtained fibers, the weight ratio of fibers to polyphenols is 4:1-2:1, and polyphenols are added to water at a ratio of 0.2 g / mL-0.5 g / mL. The polyphenols may be tea polyphenols, tannic acid, etc.

[0027] In the embodiments of the present application, the hot pressing treatment conditions can be determined according to the prior art, such as the hot pressing treatment temperature can be 60-150° C., the hot pressing treatment pressure can be 4-10 MPa, and the hot pressing treatment time can be 30-60 min.

[0028] The glue-free fiberboard prepared in the present application has excellent mechanical properties such as internal bonding strength and flexural strength, among which the internal bonding strength is 0.9-2.4MPa, the flexural strength is 19.61-28.21MPa, and the 24h water absorption thickness expansion rate is 3%-12%, which can meet the national standards.

[0029] The following is a detailed description of the non-glue fiberboard and its preparation method with specific examples, as shown below. The experimental methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are all commercially available unless otherwise specified.

[0030] Embodiment 1: A method for preparing a non-glue fiberboard comprises the following steps:

[0031] Weighing weight 0.35g / cm 3 20 g of poplar fiber was soaked in phosphate buffer and heated at 60 °C for 24 h. The phosphate buffer was made by measuring 500 mL of deionized water, 1.45 mL of sodium hypochlorite (5% effective chlorine), 0.07 g of TEMPO oxidant, 5.2 g of NaClO 2 , 3.34g phosphate buffer with pH=6.8-7.0. After the reaction is completed, add 200mL ethanol, stop the reaction for 1h, rinse with ultrapure water and soak for 24h, squeeze out the water; after mixing the clean poplar fiber with pure water, add 0.1mol / L sodium chloride, statically bond for 12h, squeeze out the water again, evenly spread tea polyphenols at a ratio of 0.2g / ml into the water and stir evenly for chelation, and then place the poplar fiber in a 10×10 mold for compaction and hot pressing treatment, the hot pressing pressure is 4MPa, the hot pressing temperature is 140℃, and the temperature is lowered after hot pressing for 45min to obtain a non-glue fiberboard.

[0032] The internal bonding strength of the glue-free fiberboard was measured to be 2.4 MPa, the flexural strength was 25.2 MPa, and the 24h water absorption thickness expansion rate was 7%.

[0033] Embodiment 2: A method for preparing a non-glue fiberboard comprises the following steps:

[0034] Weighing weight 0.40g / cm 3 20 g of poplar fiber was soaked in phosphate buffer and heated at 60 °C for 24 h. The phosphate buffer was made by measuring 500 mL of deionized water, 1.45 mL of sodium hypochlorite (5% effective chlorine), 0.07 g of TEMPO oxidant, 5.2 g of NaClO2 , 3.34g pH = 6.8 ~ 7.0 phosphate buffer. After the reaction is completed, add 200mL ethanol, stop the reaction for 1h, rinse with ultrapure water and soak for 24h, squeeze out the water; after the clean wood fiber is mixed with pure water, add 0.1mol / L sodium chloride, static bonding for 12h, squeeze out the water again, spread evenly, add tannic acid at a ratio of 0.2g / ml to the water and stir evenly for chelation, and then place the poplar fiber in a 10×10 mold for compaction and hot pressing treatment, the hot pressing pressure is 4MPa, the hot pressing temperature is 140℃, and the temperature is lowered after hot pressing for 45min to obtain a non-glue fiberboard.

[0035] The internal bonding strength of the glue-free fiberboard was measured to be 2.1 MPa, the flexural strength was 24.1 MPa, and the 24h water absorption thickness expansion rate was 6%.

[0036] Embodiment 3: A method for preparing a non-glue fiberboard comprises the following steps:

[0037] Weighing weight 0.38g / cm 3 20 g of poplar fiber was soaked in phosphate buffer and heated at 60 °C for 24 h. The phosphate buffer was made by measuring 500 mL of deionized water, 1.45 mL of sodium hypochlorite (5% effective chlorine), 0.07 g of TEMPO oxidant, 5.2 g of NaClO 2 , 3.34g pH = 6.8 ~ 7.0 phosphate buffer. After the reaction is completed, add 200mL ethanol, stop the reaction for 1h, rinse with ultrapure water and soak for 24h, squeeze out the water; after the clean wood fiber is mixed with pure water, add 0.2mol / L sodium chloride, static bonding for 12h, squeeze out the water again, spread evenly, add tea polyphenols at a ratio of 0.2g / ml to the water and stir evenly, and then place the poplar wood fiber in a 10×10 mold for compaction and hot pressing treatment, the hot pressing pressure is 4MPa, the hot pressing temperature is 140℃, and the temperature is lowered after hot pressing for 45min to obtain a non-glue fiberboard.

[0038] The internal bonding strength of the glue-free fiberboard was measured to be 2.3 MPa, the flexural strength was 25 MPa, and the 24h water absorption thickness expansion rate was 7%.

[0039] Embodiment 4: A method for preparing a non-glue fiberboard comprises the following steps:

[0040] Weighing weight 0.30g / cm 3 20 g of poplar fiber was soaked in phosphate buffer and heated at 60 °C for 24 h. The phosphate buffer was made by measuring 500 mL of deionized water, 1.45 mL of sodium hypochlorite (5% effective chlorine), 0.07 g of TEMPO oxidant, 5.2 g of NaClO 2, 3.34g pH = 6.8 ~ 7.0 phosphate buffer. After the reaction is completed, add 200mL ethanol, stop the reaction for 1h, rinse with ultrapure water and soak for 24h, squeeze out the water; after the clean wood fiber is mixed with pure water, add 0.2mol / L sodium chloride, static bonding for 12h, squeeze out the water again, spread evenly, add tea polyphenols at a ratio of 0.2g / ml to the water and stir evenly, and then place the poplar wood fiber in a 10×10 mold for compaction and hot pressing treatment, the hot pressing pressure is 4MPa, the hot pressing temperature is 140℃, and the temperature is lowered after hot pressing for 45min to obtain a non-glue fiberboard.

[0041] The internal bonding strength of the glue-free fiberboard was measured to be 2.1 MPa, the flexural strength was 25.1 MPa, and the 24h water absorption thickness expansion rate was 6%.

[0042] Embodiment 5: A method for preparing a non-glue fiberboard comprises the following steps:

[0043] Weighing weight 0.40g / cm 3 20 g of pine fiber was soaked in phosphate buffer and heated at 60 °C for 24 h. The phosphate buffer was made by measuring 500 mL of deionized water, 1.45 mL of sodium hypochlorite (5% effective chlorine), 0.07 g of TEMPO oxidant, 5.2 g of NaClO 2 , 3.34g pH = 6.8 ~ 7.0 phosphate buffer. After the reaction is completed, add 200mL ethanol, stop the reaction for 1h, rinse with ultrapure water and soak for 24h, squeeze out the water; after the clean wood fiber is mixed with pure water, add 0.2mol / L sodium chloride, static bonding for 12h, squeeze out the water again, spread evenly, add tea polyphenols at a ratio of 0.2g / ml to the water, stir evenly, compact in a 10×10 mold, and perform hot pressing treatment. The hot pressing pressure is 4MPa, the hot pressing temperature is 120℃, and the temperature is lowered after hot pressing for 60min to obtain a non-glue fiberboard.

[0044] The internal bonding strength of the glue-free fiberboard was measured to be 2.0 MPa, the flexural strength was 24.5 MPa, and the 24h water absorption thickness expansion rate was 6%.

[0045] Embodiment 6: A method for preparing a non-glue fiberboard comprises the following steps:

[0046] Weighing weight 0.35g / cm 3 20 g of willow fiber was soaked in phosphate buffer and heated at 60 °C for 24 h. The phosphate buffer was made by measuring 2000 mL of deionized water, 5.8 mL of sodium hypochlorite (5% effective chlorine), 0.28 g of TEMPO oxidant, 20.8 g of NaClO 2, 13.36g pH = 6.8 ~ 7.0 phosphate buffer. After the reaction is completed, add 800mL ethanol, stop the reaction for 1h, rinse with ultrapure water and soak for 24h, squeeze out the water; after the clean wood fiber is mixed with pure water, add 0.2mol / L sodium chloride, static bonding for 12h, squeeze out the water again, spread evenly, add tea polyphenols at a ratio of 0.2g / ml to the water, stir evenly, compact in a 20×20 mold, and perform hot pressing treatment, the hot pressing pressure is 4MPa, the hot pressing temperature is 140℃, and the temperature is lowered after hot pressing for 60min to obtain a non-glue fiberboard.

[0047] The internal bonding strength of the glue-free fiberboard was measured to be 2.1 MPa, the flexural strength was 24.8 MPa, and the 24h water absorption thickness expansion rate was 7%.

[0048] Embodiment 7: A method for preparing a non-glue fiberboard comprises the following steps:

[0049] Weighing weight 0.35g / cm 3 40 g of willow fiber was soaked in phosphate buffer and heated at 60 °C for 24 h. The phosphate buffer was made by measuring 2000 mL of deionized water, 5.8 mL of sodium hypochlorite (5% effective chlorine), 0.28 g of TEMPO oxidant, 20.8 g of NaClO 2 , 13.36g pH = 6.8 ~ 7.0 phosphate buffer. After the reaction is completed, add 800mL ethanol, stop the reaction for 1h, rinse with ultrapure water and soak for 24h, squeeze out the water; after the clean wood fiber is mixed with pure water, add 0.2mol / L sodium chloride, static bonding for 12h, squeeze out the water again, spread evenly, add tea polyphenols at a ratio of 0.2g / ml to the water, stir evenly, compact in a 20×20 mold, and perform hot pressing treatment, the hot pressing pressure is 4MPa, the hot pressing temperature is 140℃, and the temperature is lowered after hot pressing for 60min to obtain a non-glue fiberboard.

[0050] The internal bonding strength of the glue-free fiberboard was measured to be 2.0 MPa, the flexural strength was 20.8 MPa, and the 24h water absorption thickness expansion rate was 9%.

[0051] Embodiment 8: A method for preparing a non-glue fiberboard comprises the following steps:

[0052] Weighing weight 0.35g / cm 3 40 g of willow fiber was soaked in phosphate buffer and heated at 60 °C for 24 h. The phosphate buffer was made by measuring 2000 mL of deionized water, 5.8 mL of sodium hypochlorite (5% effective chlorine), 0.28 g of TEMPO oxidant, 20.8 g of NaClO 2, 13.36g pH=6.8~7.0 phosphate buffer. After the reaction is completed, add 800mL ethanol, stop the reaction for 1h, rinse with ultrapure water and soak for 24h, squeeze out the water; after the clean wood fiber is mixed with pure water, add 0.2mol / L sodium chloride, statically bond for 12h, squeeze out the water again, spread evenly, add tea polyphenols at a ratio of 0.2g / ml to the water, stir evenly, compact in a 20×20 mold, and perform hot pressing treatment, the hot pressing pressure is 8MPa, the hot pressing temperature is 140℃, and the temperature is lowered after hot pressing for 60min to obtain a non-glue fiberboard.

[0053] The internal bonding strength of the glue-free fiberboard was measured to be 2.4 MPa, the flexural strength was 28.8 MPa, and the 24h water absorption thickness expansion rate was 5%.

[0054] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

[0055] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a glue-free fiberboard, characterized in that: include: The wood fiber is subjected to oxidation treatment to obtain an intermediate; The intermediate is placed in a metal ion solution for non-covalent coordination treatment, the solution is squeezed out, and polyphenol is added to the obtained fiber for chelation to obtain chelated fiber; The chelated fibers are assembled into a board blank, and subjected to a heat pressing treatment to obtain a non-glue fiberboard.

2. The method for preparing the glue-free fiberboard according to claim 1, characterized in that: The non-covalent coordination treatment time is 6-24h.

3. The method for preparing the glue-free fiberboard according to claim 1, characterized in that: The mass ratio of the fiber to the polyphenol is 4:1-2:

1.

4. The method for preparing the glue-free fiberboard according to claim 1, characterized in that: The metal ion solution is one or more of a sodium chloride solution, an aluminum chloride hexahydrate solution, and a cobalt chloride hexahydrate solution.

5. The method for preparing the glue-free fiberboard according to claim 1, characterized in that: The step of oxidizing the wood fiber to obtain the intermediate comprises: The wood fiber is immersed in a chemical solution, subjected to a heating and oxidation treatment, and washed to obtain an intermediate.

6. The method for preparing the glue-free fiberboard according to claim 5, characterized in that: The chemical solution is a mixed aqueous solution of phosphate buffer solution, sodium chlorite, 2,2,6,6-tetramethylpiperidinyl oxide and sodium hypochlorite, or a mixed aqueous solution of sodium chloride and tea polyphenols.

7. The method for preparing the glue-free fiberboard according to claim 1 or 5, characterized in that: The oxidation treatment temperature is 50-90°C, and the oxidation treatment time is 1-24h.

8. The method for preparing the glue-free fiberboard according to claim 1, characterized in that: The hot pressing treatment temperature is 60-150°C, the hot pressing treatment pressure is 4-10MPa, and the hot pressing treatment time is 30-60min.

9. The method for preparing the glue-free fiberboard according to claim 1, characterized in that: The glue-free fiberboard has an internal bonding strength of 0.9-2.4 MPa, a bending strength of 19.61-28.21 MPa, and a 24-hour water absorption thickness expansion rate of 3%-12%.

10. A glue-free fiberboard, characterized in that: The glue-free fiberboard is prepared by the method for preparing the glue-free fiberboard according to any one of claims 1-9.

Citation Information

Patent Citations

  • Adhesive-free fiberboard and preparation method thereof

    CN117464800A

  • Gluing-free middle and high-density fiber board preparation method

    CN101086150A

  • Complex plant fiber, complex fiber board and manufacturing method thereof

    CN110509368A

  • Environment-friendly lignin composite board and preparation method thereof

    CN115489172A

  • Glue-free straw fiber board and preparation method thereof

    CN117484631A

Cited By

  • Adhesive-free shaving board and preparation method thereof

    CN120422325A

  • Fiber pretreatment method for preparing binderless fiberboard

    CN120503290A

  • Glue-free cork board and preparation method thereof

    CN120552172A

  • Preparation method of glue-free glued fiberboard based on metal chelation

    CN120572599A

  • Environment-friendly fiberboard based on grading treatment of fiber raw materials and preparation method thereof

    CN122100286A